2013
DOI: 10.1016/j.nicl.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the DemTect in Alzheimer's disease and frontotemporal lobar degeneration – A combined MRI & FDG-PET study

Abstract: Valid screening devices are critical for an early diagnosis of dementia. The DemTect is such an internationally accepted tool. We aimed to characterize the neural networks associated with performance on the DemTect's subtests in two frequent dementia syndromes: early Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD). Voxel-based group comparisons of cerebral glucose utilization (as measured by F-18-fluorodeoxyglucose positron emission tomography) and gray matter atrophy (as measured by stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 83 publications
4
18
0
1
Order By: Relevance
“…Although this fact might suggest a chronological process in bvFTD, this could not be confirmed with our data sample, as the investigated MRI and FDG-PET cohorts did only partly overlap. Accordingly, further longitudinal studies have to explore whether the different imaging approaches mirror a topographical and chronological hierarchical ‘nexopathic’ model as suggested for Alzheimer’s disease previously, where regional hypometabolism, presumably due to diaschisis/disconnection effects, is followed by regional atrophy (Chételat et al, 2008; Dukart et al, 2013b; Jack et al, 2010; Villain et al, 2008; Woost et al, 2013). The (meta-analytically) identified prototypical networks might be used as ‘hubs or networks of interest’ to increase individual diagnostic accuracy based on multimodal imaging and machine learning algorithms such as support vector machine classification (Dukart et al, 2011, 2013a), and to further the disease’s understanding with connectivity analyses (Farb et al, 2013; Filippi et al, 2013; Jech et al, 2013; Mueller et al, 2013; Seeley et al, 2009; Warren et al, 2012; Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although this fact might suggest a chronological process in bvFTD, this could not be confirmed with our data sample, as the investigated MRI and FDG-PET cohorts did only partly overlap. Accordingly, further longitudinal studies have to explore whether the different imaging approaches mirror a topographical and chronological hierarchical ‘nexopathic’ model as suggested for Alzheimer’s disease previously, where regional hypometabolism, presumably due to diaschisis/disconnection effects, is followed by regional atrophy (Chételat et al, 2008; Dukart et al, 2013b; Jack et al, 2010; Villain et al, 2008; Woost et al, 2013). The (meta-analytically) identified prototypical networks might be used as ‘hubs or networks of interest’ to increase individual diagnostic accuracy based on multimodal imaging and machine learning algorithms such as support vector machine classification (Dukart et al, 2011, 2013a), and to further the disease’s understanding with connectivity analyses (Farb et al, 2013; Filippi et al, 2013; Jech et al, 2013; Mueller et al, 2013; Seeley et al, 2009; Warren et al, 2012; Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All the default choices of SPM8 were followed with one exception. Since it has been shown that the use of the tracer unmatched PET template to normalize brain scans may generate inconsistent results [24] and because the default SPM brain PET template is an H 2 15 O template, a customized brain FDG PET template was used [24].…”
Section: F-fdg Pet Protocol and Preprocessingmentioning
confidence: 99%
“…In another study a substantial overlap between hypometabolism and GM density reduction comparing MAPT gene carriers and noncarriers was found, but comparisons with healthy controls were not carried out [29]. In 14 patients with mild but overt FTD, including all FTD subtypes, atrophy and hypometabolism showed a greater overlap than in subjects with subjective cognitive impairment [15], but again FDG PET was more accurate than structural MRI in differentiating these 14 patients from controls [30]. Also, in FTD-amyotrophic lateral sclerosis complex a considerable overlap between atrophy and hypometabolism was found but hypometabolism exceeded atrophy in several regions [31].…”
Section: Hypometabolism and Gm Density Reduction In Predementia Bvftdmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose metabolism in frontal, parietal, and temporal lobes has been found to distinguish healthy aging adults from those diagnosed with Alzheimer disease, with 89% sensitivity and 86% specificity (10). 18 F-FDG PET has also demonstrated differences between Alzheimer and frontotemporal dementia (11), the latter of which is characterized by patterns of executive dysfunction (12) similar to those observed in adult survivors of childhood ALL (3). Frontotemporal dementia appears related to dysfunction in the frontostriatal circuit (12), a network involving reciprocal connections between dorsolateral frontal lobe regions and the basal ganglia.…”
mentioning
confidence: 95%